Neurodiversity in Classroom Dynamics: Inclusive Pedagogical Frameworks for Neurodivergent Student Engagement - Chris, Bailey; Stephanie , Petty (Mutiara Intelektual Indonesia Press, 2025)
The increasing recognition of neurodiversity in educational settings has catalyzed a transformative shift in pedagogical approaches, challenging traditional deficit-focused models and advocating for inclusive frameworks that cater to diverse cognitive profiles. With approximately 20% of children in the United States identified as neurodivergent, including conditions such as autism, ADHD, and Tourette's syndrome, there is a critical need to develop nuanced educational strategies that accommodate and celebrate cognitive diversity. The research objectives were twofold: (1) to investigate how inclusive pedagogical frameworks can effectively support the diverse learning needs of neurodivergent students, and (2) to explore systemic strategies that educational institutions can adopt to create supportive, adaptive learning environments. This study employed a comprehensive mixed-methods approach, integrating quantitative surveys, assessments, and qualitative interviews to capture both measurable outcomes and personal narratives. The research identified a significant gap in understanding how targeted interventions can be effectively tailored to meet the diverse needs of neurodivergent individuals. Key findings revealed a robust correlation coefficient of 0.826, indicating a strong positive relationship between inclusive teaching approaches and student success. The R-squared value of 0.683 suggests that 68.3% of the variance in student success can be explained by adaptive teaching methodologies. The study highlights the importance of recognizing neurodiversity as a natural variation in human cognition, emphasizing the need for systemic changes in pedagogical practices, teacher training, and policy implementation. By prioritizing individualized approaches and embracing a strengths-based perspective, educational institutions can cultivate environments that not only accommodate but celebrate the diverse ways neurodivergent students engage with learning. Ultimately, this research contributes practical insights to transform educational practices, foster inclusivity, and support the holistic development of neurodivergent learners.